2022
DOI: 10.3389/fpsyt.2022.926084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Manic Episodes After SARS-CoV-2 Contagion or COVID-19

Abstract: As COVID-19 pandemic spread all over the world, it brought serious health consequences in every medical field, including mental health. Not only healthcare professionals were more prone to develop anxiety, depression, and stress, but the general population suffered as well. Some of those who had no prior history of a psychiatric disease developed peculiar symptoms following infection with SARS-CoV-2, mostly because of psychological and social issues triggered by the pandemic. People developed traumatic memorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
(76 reference statements)
0
9
0
1
Order By: Relevance
“…A review [53] assessed the evidence on COVID-19 infection as a trigger for relapse or for onset of a bipolar disorder. Evidence of manic episodes related to COVID-19 infection was found, and decreased social interaction was identified as one of the possible explanatory mechanisms.…”
Section: Research During the Coronavirus Disease 2019 Pandemicmentioning
confidence: 99%
“…A review [53] assessed the evidence on COVID-19 infection as a trigger for relapse or for onset of a bipolar disorder. Evidence of manic episodes related to COVID-19 infection was found, and decreased social interaction was identified as one of the possible explanatory mechanisms.…”
Section: Research During the Coronavirus Disease 2019 Pandemicmentioning
confidence: 99%
“…There is growing evidence that COVID-19 and psychiatric diagnoses have a complex bidirectional relationship, each acting as an independent risk factor for the other [ 8 ]. A recent review, however, discovered evidence of multiple cases in which a patient with no known past psychiatric history was diagnosed with a first manic episode shortly after the SARS-CoV-2 infection [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The illness itself has enormous potential to serve as a trigger for an underlying bipolar disorder that is yet to be diagnosed. In the above-mentioned systematic review, almost every patient included had a history of psychiatric illness in a first-degree relative [ 9 ]. Although much is still unknown about bipolar disorder and mania, a strong genetic component has been identified [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has been found to be related to cytokine dysregulations, tryptophan metabolism alterations, sleep disorders, and structural changes in the CNS that are similar to BD ( Lorkiewicz and Waszkiewicz, 2022 ). It is suggested that all these changes may trigger or unmask the development of BD ( Lorkiewicz and Waszkiewicz, 2022 , Del Casale et al, 2022 ). In addition, our patient had a severe illness which may be related to the emergence of neuropsychiatric manifestations, which are considered to worsen the prognosis.…”
Section: Discussionmentioning
confidence: 99%